PENINGKATAN PERAN KADER DALAM PENDAMPINGAN IBU HAMIL GUNA PENCEGAHAN ANEMIA - Septi Indah Permata Sari; Juraida Roito Harahap; Siska Helina (Jurusan Kebidanan Poltekkes Kemenkes Riau, 2023)
In Indonesia, the incidence of anemia in pregnant women is still high and has increased before in 2007 as much as 24.5% in 2013 as much as (37.1%) and rose to (48.9%) in 2018 (Riskesdas , 2018). Based on Pekanbaru City Health data in 2017, the prevalence of anemia in pregnant women was 8.1%, but in 2018 the prevalence of anemia in pregnant women increased by 11.2% (Pekanbaru City Health Office, 2018). Based on data obtained by researchers from the Pekanbaru City Health Office in 2019, at the Umbansari Health Center the prevalence of anemia was quite large, namely 16.7% of the total number of pregnant women as many as 1084 people, so it is estimated that there are 196 pregnant women who suffer from anemia in pregnancy (Dinkes). Pekanbaru City, 2019). Various efforts have been made to reduce the prevalence of anemia in Indonesia, including the provision of blood-added tablets, routine counseling during ANC visits, checking Hb levels, and socialization through electronic media. This Community Service aims to improve the knowledge and skills of cadres in preventing anemia. The form of science and technology as outlined in this community service is Social Engineering, by providing training to Posyandu Cadres so that there is a pattern of technology transfer from health workers to the community. This training activity was conducted face-to-face 5 times. The activity begins by equipping the cadres with knowledge about pregnancy, anemia, ANC, nutrition for pregnant women, helminthiasis, TTD and checking Hb levels. The next stage is to assist cadres in applying the knowledge and skills acquired in health education to pregnant women and in pairs. Based on the results of the service, it was found that there was an increase in knowledge about Anemia in the cadre group. The results of the post test showed an increase in the average knowledge between the pretest and posttest. The results of observations of Health cadres in conducting Health Education to pregnant women in the class of pregnant women are in the good category. Keywords: Anemia, Cadres, Pregnant Women